39Ar dating with small samples provides new key constraints on ocean ventilation. Issue 1 (December 2018) - Ebser, Sven; Kersting, Arne; Stöven, Tim; Feng, Zhongyi; Ringena, Lisa; Schmidt, Maximilian; Tanhua, Toste; Aeschbach, Werner; Oberthaler, Markus
Abstract Ocean ventilation is the integrated effect of various processes that exchange surface properties with the ocean interior and is essential for oxygen supply, storage of anthropogenic carbon and the heat budget of the ocean, for instance. Current observational methods utilise transient tracers, e.g. tritium, SF6, CFCs and14 C. However, their dating ranges are not ideal to resolve the centennial-dynamics of the deep ocean, a gap filled by the noble gas isotope39 Ar with a half-life of 269 years. Its broad application has been hindered by its very low abundance, requiring 1000 L of water for dating. Here we show successful39 Ar dating with 5 L of water based on the atom-optical technique Atom Trap Trace Analysis. Our data reveal previously not quantifiable ventilation patterns in the Tropical Atlantic, where we find that advection is more important for the ventilation of the intermediate depth range than previously assumed. Now, the demonstrated analytical capabilities allow for a global collection of39 Ar data, which will have significant impact on our ability to quantify ocean ventilation. The rare noble gas isotope39 Ar is the ideal tracer to investigate the ventilation of the deep ocean in the time range of 50 to 1000 years. Here the authors constrain transit time distributions in the eastern Tropical Atlantic with39 Ar-measurements done on a sample size of 5 L of water utilising modern atom-optical techniques.